Analisis Minat Penggunaan E-Wallet Gopay dengan Pendekatan Model UTAUT2 - Lina Fatimah Lishobrina; Hanu Handriadma; Arlan Lapiga Bangun Zebua (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2023)
Analysis of User Interest in Using Gopay E-Wallet with UTAUT2 Model Approach - Technological and economic developments have resulted in consumer behavior patterns changing from cashless to cashless. The widespread use of cashless e-wallet transactions is due to the emergence of many service providers, one of which is Gopay. Consumer behavior patterns in technology have the potential to utilize as measured by several models. The Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) is used as a model. The objective of this research is to analyze consumer usage behavior of e-wallet services (Usage Behavior) interest in using e-wallet services consumer behavior intentions. Gopay uses the UTAUT2 model. The analysis of this usage behavior model is measured using 6 independent variables, namely performance expectations, effort expectations, social influence, conditions of support, motivation, and hedonic has on the dependent variable usage behavior by examining the effect of intermediary variables on behavior. As well as the intent to use IPMA To evaluate the relevance of each independent variable and its effectiveness about the dependent variable. The methodology employed in this study is quantitative research. Non-probability sampling and purposive sampling are the sampling techniques that have been utilized. The sample size is 400 respondents and the respondent's information is from the survey. The results of this survey were processed with SmartPLS 3.0 with the calculation results of Achievement Expectancy -0.008, EE0.056, Social Impact 0.008, HM0.118, Enabling Condition 0.176, HA Behavioral Intention, 0.4039. Then it is concluded that efficiency expectations, effort expectations, social influence, and HM do not affect user behavior through behavioral intentions. However, BI influences user behavior.